Assessment of middle-class Libyans on the quality of good governance - Kamba, Ibrahim Noureddin (2014)
The purpose of this study to assess the level of Good Governance Indicators (Political stability, government effectiveness, and control of corruption) in Libya, to analyze the differences between perception‘s of each of (Job Categories, Job Positions, and Job Experience) of Middle-Class Libyans on these Indicators in Libya, and to recommend some improvements of Good Governance in Libya. Numerous hypotheses and questions were adopted for achieving to the study objectives. Survey instrument were distributed to the respondents (N = 400) comprising of Middle-Class in the governmental sector, private sector, civil society, and academics. Data analysis started with evaluating data reliability, and ANOVA test to assess the hypotheses. For the assessment the Good Governance level, the respondent‘s answers on the questions of each of Good Governance Indicators which assessed by the mean for aiming to reach to assessment the level of Good Governance in Libya. Besides used the interviews with some of who are responsible in the Libyan government, private sector, and civil society for getting their perceptions about Good Governance situation in Libya. World Bank reports about Good Governance in Libya during (1996-2010) also used for supporting the findings which obtained by the survey and the interviews. However, the study found that, there is agreement on the weakness of Good Governance of adopted indicators of this study in Libya, and there are some differences in the perceptions of respondents about the application of indicators of Good Governance in Libya. Finally, several recommendations and implications were drawn from the study.